Prevention of Hepatocellular Carcinoma by Statins: Clinical Evidence and Plausible Mechanisms - Kim, Gyuri; Kang, Eun Seok (Seminars in Liver Disease, 2019)
Statins, or 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors, are widely used to treat hypercholesterolemia for primary and secondary prevention of cardiovascular disease. Statins inhibit HMG-CoA reductase, the rate-limiting step in cholesterol synthesis, and modulate the downstream signaling of the mevalonate pathway. In addition to the primary effect, the antitumor effect of statins can be associated with mevalonate pathway-mediated and nonmevalonate pathway-mediated mechanisms, which improve endothelial function and lead to proapoptotic, antiproliferative, antiinflammatory, and antifibrotic properties. Statins are implicated in the improvement of metabolic status. Statins are orally available and safely and widely used for long-term treatment; they represent a novel approach for the prevention and treatment for hepatocellular carcinoma (HCC). Although several observational studies and experimental studies have revealed the preventive and therapeutic potential of statins for HCC treatment, further prospective interventional studies and randomized control trials are warranted to confirm these observations.
Keywords: statin; hepatocellular carcinoma; risk; prevention; pathogenesis